Cattle predation by jaguars and pumas in the Pantanal: characteristics, dynamics and the conflict with ranchers - Cavalcanti, Sandra; Crawshaw Jr., Peter Gransden; Marchini, Silvio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The Pantanal is an important area for the conservation of the jaguar (Panthera onca) and the puma (Puma concolor). However, the biome has peculiarities that make the conservation of jaguars and pumas complex and challenging. Cattle predation generates conflicts between these big cats and ranchers, which traditionally result in the opportunistic yet systematic persecution of the predators. On the other hand, there is a growing recognition among ranchers of the need to conserve jaguars and pumas, as long as the damage they cause is resolved, or at least reduced to tolerable levels. In this context, it is important to understand the dynamics of predation in order to identify actions that can effectively reduce its economic impact. Cultural aspects are also of great importance, directly influencing the decision to slaughter a jaguar or a puma or tolerate its presence. In this article we present and discuss the characteristics and dynamics of predation of native species and domestic cattle by big cats in the Pantanal, in particular the jaguar. In addition, we describe personal, social and cultural aspects of the conflict, and discuss their implications for the conservation of jaguars and pumas, highlighting the importance of understanding and involving the different actors involved in the conservation of these species.
Keywords: Problem animal; Human-wildlife conflict; Human dimensions; Wildlife monitoring; Pantaneiro; Panthera onca